Knowledge and attitude towards organ donation: a study among medical and nursing students of a medical college - Ghose, T. K.; Deo, Jayant; Dutt, Vipul; Agarwal, Raju; Patel, Barun Bhai; Ganesh, Madne; More, V. K.; Pandya, Kapil H.; Sharma, Rekha; Sharma, Dinesh; Singh, Harpreet (International Journal Of Community Medicine And Public Health, 2021)
Background: Organ transplantation is one such field of modern medical sciences which has progressed over the years and has given hope for those suffering with end stage organ diseases. There are lot of advancement in technology to preserve and transplant of organs but with this technological advancement also there are still gaps in awareness regarding the subjects. To find the gaps this study was carried out in medical college students. Methods: A cross-sectional analytical study was conducted in medical college of Pune. 400 students were included in study with keeping 50% of prevalence about awareness in mind. Tool of data collection was a pre-structured questionnaire. Frequency, percentage, and chi square test Chi-square test for linear trend and was used to find association Results: The 308 (77%) MBBS students and 92 (23%). Nursing students of all batches were included in the study. The 49.3% were aware about brain death, 68% students had fair knowledge and 10% had good knowledge about organ donation issues. The 82% students were positive, 94.5% students opined positively on policy on promotion of organ donation. The 52% students were ready to donate to anyone, while 30% students preferred to donate their organs to family members, 16% were ready to donate to their friends. Conclusions: Encouraging level of knowledge regarding organ donation, its legislative implications were present in medical and nursing students which was brought in this study.